2005
DOI: 10.1038/sj.gene.6364183
|View full text |Cite
|
Sign up to set email alerts
|

Disease association of two distinct interleukin-18 promoter polymorphisms in Caucasian rheumatoid arthritis patients

Abstract: Interleukin (IL)-18 is an important mediator of innate and adaptive immunity. We searched for an association of IL-18 promoter single-nucleotide polymorphisms (SNP) with rheumatoid arthritis (RA) in Caucasians. The entire study population was composed of two independent cohorts from Germany (n ¼ 200) and Scotland (n ¼ 410). Presence of IL-18 SNP at positions À607 and À137 was determined by allele-specific PCR in 327 RA patients and 283 healthy donors (HD). Diplotype distributions of both loci were in Hardy-Wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 32 publications
3
29
1
1
Order By: Relevance
“…Huang et al, [27] reported that IL-18-607 polymorphism was associated with RA, but not with IL-18-137 polymorphisms. Gracie et al, [28] reported that both SNPs found at positions -137 and -607 were involved in pathogenesis of RA. When other auto immune diseases were considered, the results were found to be very conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al, [27] reported that IL-18-607 polymorphism was associated with RA, but not with IL-18-137 polymorphisms. Gracie et al, [28] reported that both SNPs found at positions -137 and -607 were involved in pathogenesis of RA. When other auto immune diseases were considered, the results were found to be very conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…43 However, in Caucasian RA patients, the conclusion is not the same in Chinese RA patients. 44 The À607C-137C haplotype was more prevalent in German RA and in Scottish RA patients than in the controls. In both German and Scottish population, both SNPs at position À607 and À137 contribute to the genetic background of RA pathogenesis.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, the conclusion is that studied polymorphisms within the IL-18 promoter region do not play a major role in RA predisposition. Gracie et al (2005) found that the -607C/-137C haplotype was more prevalent in Caucasian RA patients than in a control group and concluded that SNP of both positions contribute to the genetic background of RA pathogenesis. Lee et al (2007) reported a significantly higher frequency of the 105A allele of the IL-18-105A/C SNP in Chinese rheumatoid arthritis patients compared with controls.…”
Section: Discussionmentioning
confidence: 99%